Long-term basin-scale hydropower expansion under alternative scenarios in a global multisector model. (1st November 2022) - Zhang, Ying; Binsted, Matthew; Iyer, Gokul; Kim, Sonny; Wild, Thomas; Zhao, Mengqi
Abstract: Hydropower is an important source of renewable, low-carbon energy. Global and regional energy systems, including hydropower, may evolve in a variety of ways under different scenarios. Representation of hydropower in global multisector models is often simplified at the country or regional level. Some models assume a fixed hydropower supply, which is not affected by economic drivers or competition with other electricity generation sources. Here, we implement an endogenous model of hydropower expansion in the Global Change Analysis Model, including a representation of hydropower potential at the river basin level to project future hydropower production across river basins and explore hydropower's role in evolving energy systems both regionally and globally, under alternative scenarios. Each scenario utilizes the new endogenous hydropower implementation but makes different assumptions about future low-carbon transitions, technology costs, and energy demand. Our study suggests there is ample potential for hydropower to expand in the future to help meet growing demand for electricity driven by socioeconomic growth, electrification of end-use sectors, or other factors. However, hydropower expansion will be constrained by resource availability, resource location, and cost in ways that limit its growth relative to other technologies. As a result, all scenarios show a generally decreasing share of hydroelectricity over total electricity generation at the global level. Hydropower expansion varies across regions, and across basins within regions, due to differences in resource potential, cost, current utilization, and other factors. In sum, our scenarios entail hydropower generation growth between 36% and 119% in 2050, compared to 2015, globally.